The positioning and suitability of the internal audit function to perform the assessment of organisational culture - Sithubi, Ropfiwa (College of Accounting, 2021)
This study sets out a qualitative assessment of the positioning and suitability of the Internal Audit Function (IAF) to perform the assessment of organisational culture within their entities. Literature relating to management science, social psychology and the Internal audit profession was analysed prior to conducting interviews with Chief Audit Executives (CAEs) and Audit Committee Chairpersons across various industries and sectors, to determine their perspectives on: 1. Establishing the definition of organisational culture. 2. Identifying what the key drivers of organisational culture are for the various organisations and assessing how it compares to theoretical framework(s) identified. 3. Determining the characteristics of the IAF that will determine whether or not the IAF is in a position to carry out these assessments. The results show varying perspectives on the definition of organisational culture, pointing to the complexity that is inherent in the process of defining culture. Participants identified key drivers of organisational culture within their organisations which were in line with those identified in the theoretical framework(s) identified, and further identified additional factors that they viewed as resulting in an impact on organisational culture. The results also point to the independence of the IAF placing them in a suitable position to perform the assessment of organisational culture, however, the background education and training they currently undergo is perceived not to provide the suitable skills to perform the assessment of organisational culture.